1999
DOI: 10.1038/sj.onc.1202865
|View full text |Cite
|
Sign up to set email alerts
|

Transforming growth factor-β regulates Kit ligand expression in rat ovarian surface epithelial cells

Abstract: In preparation for ovulation, paracrine communication between the preovulatory follicle and overlying theca/ stromal cells and ovarian surface epithelium (OSE) must take place to facilitate the degradative and apoptotic events associated with ovulation. Kit tyrosine kinase receptors and their ligand, kit ligand (KL) are expressed within ovarian follicles, and ligand-induced receptor activation appears to account for some of the cell ± cell interactions important for oocyte development. We investigated the expr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
11
1

Year Published

2000
2000
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 52 publications
2
11
1
Order By: Relevance
“…Transforming growth factor beta was used as a positive control and found to stimulate KGF and KL gene expression. This is in contrast to a previous observation that demonstrated that TGF␤ can inhibit the ability of cAMP to stimulate KL gene expression [55]. Whether differences in assay sensitivity or basal levels of gene expression is the reason for differences between this and the current study remains to be investigated.…”
Section: Discussioncontrasting
confidence: 84%
“…Transforming growth factor beta was used as a positive control and found to stimulate KGF and KL gene expression. This is in contrast to a previous observation that demonstrated that TGF␤ can inhibit the ability of cAMP to stimulate KL gene expression [55]. Whether differences in assay sensitivity or basal levels of gene expression is the reason for differences between this and the current study remains to be investigated.…”
Section: Discussioncontrasting
confidence: 84%
“…This may be an additional outcome of decreased epithelial levels of active TGF-␤ 1 ; TGF-␤ 1 has been shown to inhibit SCF production by ovarian epithelial cells. 61 In wild-type mice, levels of epithelial SCF transcripts did not change on infection, in agreement with previous findings in mice infected with Nippostrongylus brasiliensis. 39 SCF is a key regulator of T. spiralisinduced intestinal mastocytosis, 37,38 SCF is produced by the small intestinal epithelium 39 and has both systemic and local effects on mast cell development.…”
Section: Comparison Of Th2-driven Inflammation and Of Cd3 ϩ T-cell Posupporting
confidence: 81%
“…64 Preferential expression of KL-1 rather than KL-2 can be associated with increased production of the soluble form of SCF in epithelial cells. 61,64 Here, we have found that the KL-1 splice variant of SCF is preferentially expressed in infected ␤ 6 Ϫ/Ϫ mice in relation to KL-2, possibly favoring local production of SCF that can be more readily cleaved to its soluble form. Local up-regulation of SCF, diffusing from the epithelium, may contribute to increased proliferation of MMCs in the lamina propria of ␤ 6 Ϫ/Ϫ mice.…”
Section: Comparison Of Th2-driven Inflammation and Of Cd3 ϩ T-cell Pomentioning
confidence: 92%
“…CD117 is mostly reported in mast cells/myeloid cells (mastocytoma/acute myeloid leukemia) [18], germ cells (seminoma) [19], Cajal cell (gastrointestinal stromal tumors) [20], [21] and some epithelial cells [22], [23], [24], [25]. CD117 expression in tumor stromal cells is neglected and rarely reported.…”
Section: Discussionmentioning
confidence: 99%